2015
DOI: 10.33549/physiolres.932825
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aquaporin 1, 5 and 9 in the Ovarian Follicles of Cycling and Early Pregnant Pigs

Abstract: Aquaporins (AQPs) are water channel proteins responsible for water homeostasis and important for proper functioning of all body systems, including reproductive structures. This study was designed to determine their localization and quantitative changes in the pig ovary during different stages of the estrous cycle and early pregnancy. The expression of AQP 1, 5 and 9 proteins was determined by immunocytochemistry and Western blot analyses. AQP1 was found in the plasma membranes of capillary endothelium, AQP5 – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Moreover, this AQP was present in the granulosa and theca cells of follicular wall throughout the period of development until ovulation. Thus, this finding implies a possible involvement of AQP4 in folliculogenesis in the hen ovary similarly as it was strongly suggested for AQPs in mammalian ovaries (Grzesiak et al, 2016;McConnell et al, 2002;Sales, Lobo, Carvalho, Moura, & Rodrigues, 2013;Skowronska, Mlotkowska, Eliszewski, Nielsen, & Skowronski, 2015;Starowicz et al, 2014;Sun et al, 2007Sun et al, , 2009). These results, obtained for the first time in birds, are consistent with those previously reported in the human (Thoroddsen et al, 2011) and bovine (Williams, 2012) ovary, and extend the number of avian tissues in which presence of AQP4 has been shown, that is, the brain-a main place of AQP4 presence, proventriculus, muscle, kidney, ureter and testis (Goren, Adorján, & Kálmán, 2006;Nishimura & Yang, 2013;Saito, Ikegami, & Shimada, 2005;Skowronski, Leska, Robak, & Nielsen, 2009;Sugiura, Aste, Fujii, Shimada, & Saito, 2008;Yoshimura et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, this AQP was present in the granulosa and theca cells of follicular wall throughout the period of development until ovulation. Thus, this finding implies a possible involvement of AQP4 in folliculogenesis in the hen ovary similarly as it was strongly suggested for AQPs in mammalian ovaries (Grzesiak et al, 2016;McConnell et al, 2002;Sales, Lobo, Carvalho, Moura, & Rodrigues, 2013;Skowronska, Mlotkowska, Eliszewski, Nielsen, & Skowronski, 2015;Starowicz et al, 2014;Sun et al, 2007Sun et al, , 2009). These results, obtained for the first time in birds, are consistent with those previously reported in the human (Thoroddsen et al, 2011) and bovine (Williams, 2012) ovary, and extend the number of avian tissues in which presence of AQP4 has been shown, that is, the brain-a main place of AQP4 presence, proventriculus, muscle, kidney, ureter and testis (Goren, Adorján, & Kálmán, 2006;Nishimura & Yang, 2013;Saito, Ikegami, & Shimada, 2005;Skowronski, Leska, Robak, & Nielsen, 2009;Sugiura, Aste, Fujii, Shimada, & Saito, 2008;Yoshimura et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…The data support the proposal that the pituitary gonadotropins, prolactin and growth hormone considerably influenced AQP1 expression in the porcine ovarian follicular cells. In a previous study [ 31 ], the presence of AQP1 protein in the vascular endothelium of the entire porcine ovarian follicles during the estrous cycle and early pregnancy was demonstrated. Nonetheless, AQP1 protein expression was highest on days 18–20 of the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A study of AQPs on the pig model showed expression of AQP1, 5 and 9 in the ovary [ 27 , 31 ]. AQP1 was found in the capillary endothelium and AQP5 and AQP9 in Gc of primordial and developmental follicles.…”
Section: Introductionmentioning
confidence: 99%
“…AQPs have been divided into three groups based on their permeability properties: AQP0, 1, 2, 4, 5, 6 and 8 are classical water channels; AQP3, 7, 9 and 10 are aquaglyceroporins; AQP11 and 12 are superaquaporins (Ishibashi et al 2009). As AQP5 and 9 have been identified in the porcine ovarian follicles (Skowronski et al 2009;Skowronska et al 2015), it was suggested that they might contribute to water influx across the ovarian wall and consequently participate in the growth of the follicular antrum in pigs. Our recent in vitro studies revealed that testosterone acting via intracellular ARs increased water permeability of porcine granulosa cells, probably through the modulation of AQP activity (Grzesiak et al 2013).…”
Section: Introductionmentioning
confidence: 99%